2019
DOI: 10.3390/biom9100557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Anti-Cancer Activity of the Probiotic Bacterium Lactobacillus fermentum Using 2D vs. 3D Culture in Colorectal Cancer Cells

Abstract: The aim of this study was to investigate the potential anti-cancer effects of probiotic cell-free supernatant (CFS) treatment using Lactobacillus fermentum for colorectal cancer (CRC) in 3D culture systems. Cell viability was assessed using MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt) assays, whereas apoptosis was monitored through RT-qPCR analysis of Bax, Bak, Noxa, and Bid mRNA expressions in addition to flow cytometry analysis of Lactobacillus ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Their culture supernatants inhibited the growth of cancerous cells by up to 7% after 72 h of incubation at the concentration of 25%. Our study confirms a previous finding by Lee et al (2019), who demonstrated the antiproliferative effects of the culture-free supernatant (CFS) of a L. fermentum strain against colorectal cancer (CRC). It was shown that the CFS induces apoptosis, thereby inhibiting cell growth in CRC lines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their culture supernatants inhibited the growth of cancerous cells by up to 7% after 72 h of incubation at the concentration of 25%. Our study confirms a previous finding by Lee et al (2019), who demonstrated the antiproliferative effects of the culture-free supernatant (CFS) of a L. fermentum strain against colorectal cancer (CRC). It was shown that the CFS induces apoptosis, thereby inhibiting cell growth in CRC lines.…”
Section: Discussionsupporting
confidence: 92%
“…The antiproliferative activity of L. fermentum is brought about by preventing NF-κB signaling. They showed that the Lactobacillus CFS is capable of inducing cell death, and thus has the potential to be used as a powerful multitarget anti-cancer chemotherapeutic agent (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…P8 protein that produced by L. rhamnosus KCTC 12202BP, shows strong inhibitory effect on colon cancer cell by inducing cell cycle arrest [ 27 ]. And Lee et al evidenced the anti-cancer activity of the probiotic bacterium L. fermentum using 3D culture in colon cancer cells [ 28 ]. Moreover, Carmen et al revealed LAB shows anti-cancer effect by expressing antioxidant enzymes or IL-10 in colon cancer model mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional spheroid culture models represent in vivo cancer environments and can be used to study cell survival and drug resistance at the molecular mechanism level [ 12 ]. Three-dimensional Jurkat spheroid models were generated as described in our previous reports [ 22 , 23 ]. The cells were treated with 0.5% and 1.0% methylcellulose for 48 h and 72 h ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%